2016
DOI: 10.1177/0301006616684369
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sensory Correspondences: Heaviness is Dark and Low-Pitched

Abstract: Everyday language reveals how stimuli encoded in one sensory feature domain can possess qualities normally associated with a different domain (e.g., higher pitch sounds are bright, light in weight, sharp, and thin). Such cross-sensory associations appear to reflect crosstalk among aligned (corresponding) feature dimensions, including brightness, heaviness, and sharpness. Evidence for heaviness being one such dimension is very limited, with heaviness appearing primarily as a verbal associate of other feature co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 62 publications
0
23
1
Order By: Relevance
“…Note that size-pitch-correspondences and weight-pitch-correspondences (cf. [23,24]), as well as size-loudness correspondences [13,25] well documented. Our findings show, that when paired with a salient visual stimulus, loudness carries much more impact than does pitch.…”
Section: Discussionmentioning
confidence: 91%
“…Note that size-pitch-correspondences and weight-pitch-correspondences (cf. [23,24]), as well as size-loudness correspondences [13,25] well documented. Our findings show, that when paired with a salient visual stimulus, loudness carries much more impact than does pitch.…”
Section: Discussionmentioning
confidence: 91%
“…For example, the numbers might influence the perception of the ball's hardness, which in turn might influence the perception of weight 2 . Alternatively, larger numbers might be experienced as "higher" and smaller numbers as "lower" (e.g., Walker, Scallon, & Francis, 2017; also see Walker, Walker, & Francis, 2012, 2015, while lighter objects tend to be higher up in the environment and heavier objects tend to be lower 3 . In combination, these number-height and height-weight associations would lead to a similar pattern as observed in Experiment 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, in fact, past studies have suggested relationships between sound and shape or meaning, and a relationship between a mono mora or a phoneme and the impression evoked from it has been revealed in multiple languages [e.g., [3][4][5][6][7][8]. On the other hand, there are also many studies dealing with the phenomenon as a cross-modality, cross-sensory, or crossmodal association [e.g., [9][10][11]. In addition, there are studies about the relationships between brain functions and the cross-sensory phenomenon [e.g., [12][13][14].…”
Section: Sound Symbolismmentioning
confidence: 99%